Empyema in Children - Is Primary VATS the Preferred Strategy - Singh, Rajesh Kumar; Gurudutta, Avathi Venkatesha; Chandrasekar, Supraja; Thomas, Arun (Journal of Nepal Paediatric Society, 2020)
Introduction: Empyema thoracis (ET) is an accumulation of pus in the pleural space. Considering the advantages of Video Assisted Thoracoscopic surgery (VATS), including reduced length of hospitalisation, lower postoperative morbidity and mortality, VATS is the treatment of choice for cases of stage 3 empyema. The objective of this study was to study the age-sex profile, clinical presentation, etiologic agents, management and the overall treatment outcome of empyema thoracis after early VATS in children. Methods: This was a retrospective observational study, conducted in the Department of Paediatrics, Rangadore Memorial Hospital, Bangalore, from November 2018 to March 2020. All children in the age group of 0 to 18 years diagnosed to have pyogenic empyema and presenting in stage 1 and 2 during the study period were included in the study. In the present study, 15 children were found to be having empyema (stage 1 and 2). Results: Majority of patients (66.6%) were seen in the age group of one to five years. Fever (100%), breathlessness (66.66%), and cough (80%) were the commonest presenting features. Bacteriological isolation was possible only in three cases (20%). Patients were treated with antibiotics and primary VATS in majority of cases (55.33%). Average duration of hospital stay in VATS group was 12.11 days. Conclusions: Empyema thoracis mainly affects younger children. Common presenting features are fever, difficulty in breathing and cough. Appropriate antibiotics and early VATS may be acceptable modality for management of pyogenic empyema thoracis in children.